2013
DOI: 10.6026/97320630009610
|View full text |Cite
|
Sign up to set email alerts
|

Systems biological approach to investigate the lack of familial link between Down’s Syndrome & Neural Tube Disorders

Abstract: Systems Biology involves the study of the interactions of biological systems and ultimately their functions. Down's syndrome (DS) is one of the most common genetic disorders which are caused by complete, or occasionally partial, triplication of chromosome 21, characterized by cognitive and language dysfunction coupled with sensory and neuromotor deficits. Neural Tube Disorders (NTDs) are a group of congenital malformations of the central nervous system and neighboring structures related to defective neural tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Transcripts present in the dense clique are the most interconnected, hence, belong to the center of the etiological pathway underlying any disease. 50…”
Section: Construction Of CML and Lymphoblastoid Cerna Network And Det...mentioning
confidence: 99%
“…Transcripts present in the dense clique are the most interconnected, hence, belong to the center of the etiological pathway underlying any disease. 50…”
Section: Construction Of CML and Lymphoblastoid Cerna Network And Det...mentioning
confidence: 99%
“…DS results from an over-expression of three extra copies of the gene on chromosome 21 causing failure of normal chromosomal separation during meiosis [21,51,52]. DS affects approximately 1 in 1000 to 1100 live births worldwide and 1 out of every 700 newborns in the US [53,54]. An important risk factor for DS is advanced maternal age at the time of conception [51,52].…”
Section: Down Syndromementioning
confidence: 99%
“…Women who are 35 years or older are more at an increased risk of having a child with DS, however DS children have been born to younger mothers [55][56][57][58]. Studies have shown that mothers of children with DS have abnormal folate metabolism, high homocysteine and hypomethylation similar to NTDs, which result in abnormal gene expression and chromosomal segregation [20,50,53,59].…”
Section: Down Syndromementioning
confidence: 99%